(3GdCbhGd GdcGajI hGdaUhd GdTGajI aj GdNjd hGdaQhSjI hCeQGV GdNjd hYdGLgG hCSeGA GdNjd GdeTghQIs - (3Ydj Hf OGhO Hf jhSa Hf Ydj Hf QShd Gdjefjs ((3eMeO Hf CMeO GdeZQHi Gdeci GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg GddWja HNdbg GdeJcad dge bHd GdSDGd HSGHZ QRbg s
(3BNQgG (B:s
(3hefgG GdjefjI LHGd MjGO JfSH Edi Gdjef Jchf ai GdShGMd GdjefjI djS s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs